Physical fitness and performance standards for the Canadian army - Lee, S. W.; Chahal, Paul; Singh, Mohan; Wheeler, G. (My University, 1990)
Examines physical fitness standards and testing, with particular emphasis on the fitness requirements of the Canadian Army. The importance of physical fitness to the Canadian Army is reviewed and physical fitness tests administered in the Canadian military are analyzed. An overview of Canadian and international fitness testing includes the following tests: the Canadian Army uses CF EXPRES Programme derived from the Canadian Standardized Test of Fitness, the Battle Efficiency Test (BET), a 19-item Indoor Standardized Obstacle Course (ISOC); United States Army uses the Army Physical Readiness Test (APRT); the Australian Army utilizes the Physical Training Test (PTT), the British Army has three types of tests including the Army Personal Fitness Assessment; the Swedish Army, the Physical Working Capacity test and the Soviet Army, the GTO programme which means Ready for Labour and Defence.
Keywords: Canada; armed forces; testing; armies; physical fitness